ANALISIS KOMPARATIF KETEPATAN ALTMAN Z-SCORE DAN GROVER SCORE DALAM MEMPREDIKSI FINANCIAL DISTRESS (Studi Empiris Perusahaan Sektor Manufaktur dan Kesehatan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2021-2023) - Aurelia Maharani Putri; Yuyetta Etna Nur Afri (Diponegoro Journal of Accounting, 2025)
Financial distress is a company's financial condition that is in an unhealthy state or experiencing a crisis that can cause the company to go bankrupt. This study aims to (1) Analyze the differences in the accuracy of Altman Z-Score in predicting financial distress in manufacturing sector companies and the health sector listed on the IDX in 2021-2023 (2) Analyze the differences in the accuracy of Grover Score in predicting financial distress in manufacturing sector companies and the health sector listed on the IDX in 2021-2023. (3) Analyzing the moderation of sector type on the accuracy of Altman Z-Score (4) Analyzing the moderation of sector type on the accuracy of Grover Score.This research was conducted using quantitative methods with secondary data derived from the company's annual report. The population of this study is manufacturing sector companies and the health sector listed on the Indonesia Stock Exchange in 2021-2023. With the purposive sampling method, this study obtained 43 manufacturing sector companies and 22 health sector companies that met the criteria. This research data analysis technique uses the independent t-test and Moderated Regression Analysis (MRA).The results of this study indicate that there are differences in the accuracy of Altman Z- Score and Grover Score in the manufacturing and health sectors. This study also proves that type of sector moderate the accuracy of Altman Z-Score and Grover Score in predicting financial distress.